Cinta Yang Sepadan Dalam Perspektif Endogami: Sebuah Pembacaan Tradisi Terhadap Narasi 2 Korintus 6:14-7:1 - Jefri Andri Saputra (Institut Agama Kristen Negeri Toraja, 2022)
The writing of this article is motivated by the author's struggles regarding the failure of the concept of compatible marriage, in the definition of “one faith”, to maintain a Christian marriage. Not a few Christian families whose household ends in divorce, even though it was built on the basis of one faith or one religion. This situation motivates the writer to formulate another parameter of compatible marriage, besides “one faith”. To solve this problem, the author reinterprets the text of 2 Corinthians 6:14-7:1, in a tradition-critical approach, namely the endogamy tradition. In this paper, the author finds that in addition to spiritual or faith compatibility, compatible marriage also includes ethnic equivalence, ethical references, and socio-political paradigms. The integration of these four aspects will construct the concept of a compatible marriage and become an evaluative material for Christian marriage. Abstrak: Penulisan artikel ini dilatarbelakangi oleh pergumulan penulis mengenai kegagalan konsep pernikahan yang sepadan dalam definisi “satu iman”, untuk mempertahankan pernikahan Kristen. Tidak sedikit keluarga Kristen yang rumah tangganya berakhir dengan perceraian, padahal dibangun di atas dasar satu iman atau satu agama. Situasi ini memotivasi penulis untuk merumuskan parameter lain dari pernikahan yang sepadan, selain satu iman. Untuk menyelesaikan masalah ini, penulis melakukan reinterpretasi terhadap teks 2 Korintus 6:14-7:1, dalam pendekatan kritik tradisi, yakni tradisi endogami. Dalam tulisan ini, penulis menemukan bahwa selain kesejajaran spiritual atau iman, kesepadanan dalam pernikahan juga mencakup kesepadanan etnis, referensi etis dan paradigma sosio-politis. Integrasi dari keempat aspek ini akan mengonstruksi konsep pernikahan yang sepadan serta menjadi bahan evaluatif bagi pernikahan Kristen.